The Impact of Logistics and Key Macroeconomic Indicators on the Development of the Startup Ecosystem in Europe - Valentyna Yakubiv; Antonina Tomashevska; Iryna Piatnychuk; Liliia Turovska; Finbarr Carter (Journal of Vasyl Stefanyk Precarpathian National University)
The article highlights that the synergetic relationship between macroeconomic indicators and logistics efficiency shapes the trajectory of startup ecosystems and global economies. By leveraging tools such as the Logistics Performance Index (LPI) and the Global Startup Ecosystem Index (GIS), policymakers and business leaders gain insights into the interconnectedness of infrastructure, economic output, and innovation. The Global Knowledge Index (GKI) and Global Innovation Index (GII) further reveal the intellectual and creative capacities of nations, while GDP per capita and the Capital Investment Index (CII) underline the financial underpinnings of economic competitiveness. Much of the analysis delves into the transformative impact of modern logistics solutions. Innovative technologies like the Internet of Things (IoT) enhance supply chain visibility and efficiency, while warehouse automation and big data analytics streamline operations. Blockchain technology, with its transparency and security, fosters trust and efficiency in supply chains, a critical factor for startups seeking cost-effective and reliable logistics frameworks. Through correlation analysis, the article underscores the measurable impact of these macroeconomic and logistical elements on the growth of startup ecosystems. Countries that effectively integrate these indicators are better positioned to attract investments, nurture entrepreneurial activity, and achieve sustainable economic growth. The findings suggest that fostering a dynamic startup ecosystem requires an integrated approach, combining robust macroeconomic policies with cutting-edge logistical innovations. This strategy not only propels startups into the competitive global market but also strengthens the economic fabric and welfare of the population.